Researching organizations : the practice of organizational fieldwork - Jones, Matthew R. (Matthew Russell), 1958- (Los Angeles: SAGE, 2014)
Identifying the practicalities and key challenges of carrying out organisational research, this book introduces students across disciplines to all that is involved with this type of fieldwork.
1. Introduction -- 2. Research and organizations -- 3. The research process -- 4. Ethics in organizational research -- 5. Getting in: Seeking and negotiating access -- 6. Getting on: In the organization -- 7. Getting out: Leaving the field and reporting research in organizations -- 8. Getting back -- 9. Emerging issues in research in organizations -- 10. Conclusions.
Includes bibliographical references and index.
anannya
Keywords: Organization -- Research -- Methodology; RESEARCH - METHODOLOGY; ORGANIZATION - RESEARCH; Organization -- Research -- Methodology; Organisationsforschung; Feldforschung; Organisation; Methodologie; Society